Molecular Convergence and Liposome-Enabled Therapeutics: Integrating Mechanistic Links Between Neurodegeneration and Cancer - Molavi Rahbar, Mohammad Kazem; Karimi Forood, Amir Mohammad; Amini, Borhan; Tavasolikejani, Somayeh; Fatehi Shalamzari, Paradise; Djalolidin, Mansurov; Mirsultan, Yakubov; Dilshoda, Karomova; Komilov, Kamol; Madina, Okhunjanova (Asian Pacific Journal of Cancer Biology, 2026)
Mounting mechanistic evidence increasingly supports the notion that cancer and neurodegenerative diseases, traditionally regarded as biologically disparate entities, are in fact governed by partially overlapping molecular and cellular determinants. Both conditions are characterized by disruption of proteostatic surveillance, mitochondrial insufficiency, sustained inflammatory activation, redox disequilibrium, and maladaptive stress-response signaling, particularly involving the unfolded protein response (UPR) and DNA damage response (DDR) networks. Recognition of these shared pathological infrastructures has catalyzed a paradigm shift toward therapeutic strategies capable of simultaneously interrogating and modulating convergent disease mechanisms rather than addressing each disorder in isolation. This review integrates molecular, pharmacological, and nanomedical perspectives to delineate the intersecting signaling axes linking tumor progression with neurodegenerative decline. Particular attention is devoted to preclinical and early clinical evidence supporting advanced liposomal platforms including stealth PEGylated vesicles, ligand-functionalized constructs, and stimuli-responsive formulations that are engineered to engage shared molecular liabilities. Collectively, these systems demonstrate the capacity to restore proteostasis, attenuate neuroinflammatory signaling, reduce oxidative and genotoxic stress, optimize intracellular trafficking, and enhance mitochondrial function across both malignant and neuronal microenvironments. Convergent findings indicate that liposomal therapeutics may exert dual-functional benefits through controlled release of anti-inflammatory or redox-modulating agents, targeted modulation of ER stress and chaperone activity, correction of disease-associated metabolic reprogramming, and improved penetration of the blood–brain barrier via receptor-mediated transport mechanisms. By acting directly at the molecular intersection points common to cancer and neurodegeneration, liposomal nanocarriers thus represent a rational platform for cross-disease intervention. Taken together, liposome-enabled nanomedicine provides a translatable cross-disease platform for targeting shared molecular pathways in cancer and neurodegeneration, enabling integrated anticancer and neuroprotective therapies with improved efficacy and safety.